PEMBERDAYAAN APARATUR SEBAGAI FAKTOR PENDORONG PENINGKATAN PRESTASI KERJA PEGAWAI (SUATU STUDI DI KANTOR KECAMATAN MALALAYANG KOTA MANADO) - Simanjuntak, Coddy (Universitas Sam Ratulangi, 2013)
Quantitative analysis results Iran) this survey showed : there ore 54 officers were asked for information about the empowerment activities they had ever follow, obviously among them who earn low empowerment is 15 officers or ± 27,78 96 from entire officer. The officer who had earn empowerment by the low category are those who rarely follow coaching program. Then as much 21 officers or ± 38,89 96 who had earn empowering with moderate category, namely they sometimes follow empowerment programs. Meanwhile, as much 18 officers or ± 33,33 96 from 54 officers had earn empowerment by high category, they are often engaged empowerment activity in quantitative and qualitative, Is done directly by the headman, sub-district and the Mayor through the relevant agencies in the particular occasion. Based of the results from the description, it can be concluded that the average implementation of empowerment program has been followed by governance officer around in middle category.) Keywords : Organization, Maritim, Management